THE INFLUENCE OF SOCIODEMOGRAPHIC FACTORS, ENVIRONMENTAL CONDITIONS, AND NUTRITIONAL STATUS ON THE INCIDENCE OF TUBERCULOSIS IN KARAWANG REGENCY - Kusumah, Eva Nurhasanah; Nina, Nina (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Introduction: Pulmonary tuberculosis remains a major global health problem, especially in developing countries. Indonesia ranks second worldwide in TB incidence and, together with India, the Philippines, and South Africa, accounts for 44% of global cases. Rising case numbers are partly due to underreporting or undiagnosed patients, creating barriers to accurately determining TB incidence in Indonesia. Methods: This analytical observational study used a cross-sectional design at two community health centers (Puskesmas) in Karawang Regency, selected through random sampling: Cibuaya and Karawang Kulon. Data were obtained using a structured questionnaire and analyzed with chi-square and multiple logistic regression. Results: Logistic regression showed significant associations between gender (p < 0.001), ventilation (p < 0.001), and body mass index (BMI) (p < 0.001) with TB incidence in Karawang. BMI was the most dominant factor. Conclusion: Three variables were significantly associated with TB incidence: gender, ventilation, and BMI. Five others were not significant: age, income, family size, house size, and education. Nutrition education, supplementation programs, and access to nutritious food should be integrated into TB control efforts, along with improvements to housing conditions, particularly ventilation and size.